Effectiveness of complex interventions focused on quality-of-life assessment to improve palliative care patients' outcomes: A systematic review. (January 2015) - Catania, Gianluca; Beccaro, Monica; Costantini, Massimo; Ugolini, Donatella; De Silvestri, Annalisa; Bagnasco, Annamaria; Sasso, Loredana
Background: One of the most crucial palliative care challenges is in determining how patient' needs are defined and assessed. Assessing quality of life has been defined as a priority in palliative care, and it has become a central concept in palliative care practice. Aim: To determine to what extent interventions focused on measuring quality of life in palliative care practice are effective in improving outcomes in palliative care patients. Design: Systematic review according to the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and hand searches. Data sources: MEDLINE, CINAHL, EMBASE, PsycINFO, and the Cochrane Library were searched for articles published until June 2012, and through hand searching from references lists of included articles. Only studies that included adult palliative care patients, in any palliative care clinical practice setting of care, and with an experimental, quasi-experimental, or observational analytical study design were eligible for inclusion. All studies were independently reviewed by two investigators who scored them for methodological quality by using the Edwards Method Score. Results: In total, 11 articles (of 8579) incorporating information from 10 studies were included. Only three were randomized controlled trials. The quality of the evidence was found from moderate to low. Given a wide variability among patients' outcomes, individual effect size (ES) was possible for 6 out of 10 studies, 3 of which found a moderate ES on symptoms (ES = 0.68) and psychological (ES = 0.60) and social (ES = 0.55) dimensions. Conclusion: Effectiveness of interventions focused on quality-of-life assessment is moderate. Additional studies should explore the complexity of the real palliative care world more accurately and understand the effects of independent variables included in complex palliative care interventions.